Ultrasonographic Examination of the Rumen in Healthy Cows - Sheikh Imran; Adarsh Kumar; S. P. Tyagi; Amit Kumar; Shivali Sharma (Veterinary Medicine International)
10 healthy Indian Jersey/Red Sindhi crossbred nonpregnant cows were subjected to transabdominal ultrasonography to develop baseline topographical data of the rumen. The wall of the rumen could be identified as a thick echogenic line adjacent to the left abdominal wall from left flank to 8th intercostal space. The motility pattern of rumen was characterized by approximately 1 contraction every minute. The mean amplitude of the ruminal contraction was 3.2 cm. Ultrasonography of the rumen in healthy cows is a useful adjunct to the noninvasive diagnostic investigation of the rumen.